Color Change of Red Dragon Skin Anthocyanin Extract Biosensor for Freshness Application of Gurame Fish (Osphronemus Goramy) - Agassi, Taufik Nugraha; Putri, Pridata Gina; Ningtyas, Kurnia Rimadhanti; Deary Amethy Zahrotinufus; Fahrulsyah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Freshness of gourami fish is essential in determining the quality of fishery products because fish in fresh conditions will have good quality, so they are safe for consumption. Innovative packaging allows real-time fish freshness monitoring through color changes on the biosensor label. This study aimed to determine the color changes of the biosensor during application to the product. The results of this study, the biosensor applied to the product at a temperature of 4 ° C had a reddish-brown color until the 6th day of storage and on the 7th to 9th day it changed to greenish yellow, this is by the decrease in product quality indicated by the TVN-N value on the 7th day 19,413 mgN / 100g, the 8th 25,883 mgN / 100g and the 9th 33,650 mgN / 100g. The color of the biosensor on the 9th day is the L * value of 50.6, the a * value of 0.4, the b * value of 49.6, and the Hue value of 47 °. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production